Meningkatkan Kesadaran Konservasi Lingkungan dalam Pendidikan Biologi bagi Mahasiswa: Pendekatan Etnobiologi Berbasis Masalah Sosio-Ekologis - Defri Rahmat; Yuni Pantiwati; Yus M. Cholily; Rizki Kurniawan Rangkuti; Saprida Saprida; Wahyu Azhar Ritonga (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The background of this research is based on the global ecological crisis that demands a reform of biology education that is not only oriented towards mastery of concepts, but also on the formation of environmental conservation awareness and behavior. This research is motivated by the low conservation awareness of students in high schools which has an impact on the declining quality of the local environment. The purpose of this study is to describe the effectiveness of a socio-ecological-based ethnobiology approach in fostering environmental conservation awareness of students in biology learning. The research method used a quantitative descriptive design with 36 students as subjects. The instruments used included pre-test questions, participatory observation-based process assessment, post-test questions, and an environmental conservation awareness questionnaire. Data were analyzed using descriptive statistics and N-Gain scores. The findings showed an average pre-test score of 75.22 (SD=3.47) increasing to a post-test score of 76.00 (SD=3.66). The average process score of 59.97 reflects varied active involvement of the 36 students, 18 (50%) completed the conservation awareness questionnaire with an average score of 79.78, which is categorized as "Good." A total of 83.3% of students achieved the "Good" to "Very Good" category in the post-test. The implications of the socio-ecological-based ethnobiology approach have proven effective in integrating local wisdom with modern biological concepts, thus having the potential to be widely implemented as an innovative strategy for environmental education in Indonesia.